2018
DOI: 10.5194/acp-2018-478
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Composition of ice particle residuals in mixed phase clouds at Jungfraujoch (Switzerland): Enrichment and depletion of particle groups relative to total aerosol

Abstract: Ice particle residuals (IPRs) and the total aerosol particle population were sampled in parallel during mixed phase cloud events at the high altitude research station Jungfraujoch in January/February 2017. Particles were sampled on boron substrates by use of multi MINI cascade impactors operated behind an ice selective counterflow impactor (Ice-CVI) for IPRs and a heated total inlet for the total aerosol particles. Total aerosol samples were collected with a dilution setup to match the much longer 5 sampling t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…the station is often situated completely in the lower FT. At other times it receives variable injections of air masses originating from the PBL depending on the season and the regional weather conditions (Collaud Coen et al, 2011; Herrmann et al, 2015). Numerous BC‐related studies have already taken place at the JFJ focusing on, for example, optical properties (Lavanchy et al, 1999), nucleation scavenging (Cozic et al, 2007), and ice nucleation properties (Eriksen Hammer et al, 2018; Kupiszewski et al, 2016). Liu et al (2010) reported the first single‐particle characterization of BC at the JFJ with a single particle soot photometer (SP2).…”
Section: Introductionmentioning
confidence: 99%
“…the station is often situated completely in the lower FT. At other times it receives variable injections of air masses originating from the PBL depending on the season and the regional weather conditions (Collaud Coen et al, 2011; Herrmann et al, 2015). Numerous BC‐related studies have already taken place at the JFJ focusing on, for example, optical properties (Lavanchy et al, 1999), nucleation scavenging (Cozic et al, 2007), and ice nucleation properties (Eriksen Hammer et al, 2018; Kupiszewski et al, 2016). Liu et al (2010) reported the first single‐particle characterization of BC at the JFJ with a single particle soot photometer (SP2).…”
Section: Introductionmentioning
confidence: 99%